'Instead of "closing down" at our ages … we're thinking of exciting and challenging things to do': older people's microadventures outdoors on (e-)bikes. Issue 2 (3rd April 2019) - Spencer, Ben; Jones, Tim; Leyland, Louise-Ann; van Reekum, Carien M.; Beale, Nick
ABSTRACT: This paper explores how people aged 50 and over, who were returning to cycling as part of an 8-week health and well-being trial, created their own cycling microadventures. Applying a stage model of the process of adventure to qualitative data generated from personal diaries and focus groups, we examine how older people anticipated and prepared for their microadventures, the challenges and discoveries they experienced, the benefits they gained and how electrically assisted 'e-bikes' can provide further opportunities for adventure. We conclude that cycles are a mode uniquely placed to facilitate microadventures and that e-bikes, in particular, offer further potential to enable older people to (re-)connect with place and other people. But while this type of activity can provide benefits in terms of health and well-being, we argue that more supportive physical and social infrastructure is required to provide opportunities for more people to undertake microadventures close to their homes.